The Potassium Channel Interacting Protein 3 (DREAM/KChIP3) Heterodimerizes with and Regulates Calmodulin Function - Ramachandran, Pradeep L. (American Society for Biochemistry and Molecular Biology, 2012)
Downstream regulatory element antagonistic modulator (DREAM/KChIP3), a neuronal EF-hand protein, modulates pain, potassium channel activity, and binds presenilin 1. Using affinity capture of neuronal proteins by immobilized DREAM/KChIP3 in the presence and absence of calcium (Ca(2+)) followed by mass spectroscopic identification of interacting proteins, we demonstrate that in the presence of Ca(2+), DREAM/KChIP3 interacts with the EF-hand protein, calmodulin (CaM). The interaction of DREAM/KChIP3 with CaM does not occur in the absence of Ca(2+). In the absence of Ca(2+), DREAM/KChIP3 binds the EF-hand protein, calcineurin subunit-B. Ca(2+)-bound DREAM/KChIP3 binds CaM with a dissociation constant of ∼3 μm as assessed by changes in DREAM/KChIP3 intrinsic protein fluorescence in the presence of CaM. Two-dimensional (1)H,(15)N heteronuclear single quantum coherence spectra reveal changes in chemical shifts and line broadening upon the addition of CaM to (15)N DREAM/KChIP3. The amino-terminal portion of DREAM/KChIP3 is required for its binding to CaM because a construct of DREAM/KChIP3 lacking the first 94 amino-terminal residues fails to bind CaM as assessed by fluorescence spectroscopy. The addition of Ca(2+)-bound DREAM/KChIP3 increases the activation of calcineurin (CN) by calcium CaM. A DREAM/KChIP3 mutant incapable of binding Ca(2+) also stimulates calmodulin-dependent CN activity. The shortened form of DREAM/KChIP3 lacking the NH(2)-terminal amino acids fails to activate CN in the presence of calcium CaM. Our data demonstrate the interaction of DREAM/KChIP3 with the important EF-hand protein, CaM, and show that the interaction alters CN activity.